2019
DOI: 10.1109/access.2019.2917474
|View full text |Cite
|
Sign up to set email alerts
|

Online Bearing Fault Diagnosis Based on a Novel Multiple Data Streams Transmission Scheme

Abstract: Bearing faults are the most common failure modes in the rotating system. Vibration data from the rotating system carry important information, that is, characterization and diagnosis; therefore, the vast vibration signals collected from multiple sensors mounted in different sites are transmitted in a certain order for online fault diagnosis. However, due to the influence of transfer paths and noises, the sensitivities to the same fault signal of measured data streams are of significant differences, and signals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…The data information flow generated in the operation of smart home mainly includes two types: control data information flow and state data information flow. The control data information flow refers to the control instructions sent by the smart client device to the home terminal device [ 32 , 33 ]; Status data information flow refers to the data information that the home terminal device transmits its own status information and collected environmental information to the smart client device, and then feeds back to the user through the interactive interface. Smart home data stream transmission is shown in Figure 7 .…”
Section: Smart Home Control and Managementmentioning
confidence: 99%
“…The data information flow generated in the operation of smart home mainly includes two types: control data information flow and state data information flow. The control data information flow refers to the control instructions sent by the smart client device to the home terminal device [ 32 , 33 ]; Status data information flow refers to the data information that the home terminal device transmits its own status information and collected environmental information to the smart client device, and then feeds back to the user through the interactive interface. Smart home data stream transmission is shown in Figure 7 .…”
Section: Smart Home Control and Managementmentioning
confidence: 99%
“…To make a decision, the single mass function m r can be transformed into the probability measure BetP [23,24] defined by (5). In case of the faulty machine (B-3A), using Equation ( 5 BetP({n}) = 0 + 0.0001 2 = 0.00005 Therefore, we obtain BetP({y}) = 0.99995 probability for "yes" and BetP({n}) = 0.00005 for "no".…”
Section: In Case Of the Faultymentioning
confidence: 99%
“…In many works, it has been shown that electrical machines are subject to mechanical issues common to most rotating machines [2,3], such as mechanical imbalance [4], bearing faults [5], or resonance [6]. However, electrical machines also have their own specific problems such as stator winding faults, demagnetization of magnets, or broken rotor bars, which will produce magnetic imbalances.…”
Section: Introductionmentioning
confidence: 99%
“…Shen et al [31] proposed a new penalty domain selection machine (PDSM) transfer learning model for gearbox fault recognition. Tong et al [32] proposed Fault Sensitivity Assessment Model (FSAM) based on the Maximum Mean Difference (MMD) to transmit the most sensitive data stream, and then analyze the fault.…”
Section: Introductionmentioning
confidence: 99%